THE LEADERSHIP ROLE OF THE PRINCIPAL IN IMPROVING THE QUALITY OF EDUCATION AT MTS MANBATUL FIKRI CURUGRENDENG - Agus; Alwi Sofyan Al-giffari, Debi Putri Serena, Afif Nurseha (Adisam Publisher, 2024)
This study aims to analyze the leadership role of the principal in improving the quality of education at MTs Manbatul Fikri Curugrendeng. This study uses a qualitative approach by collecting data through interviews and observations of the school principal. Data analysis was performed using a phenomenological approach. The results of the study show that the principal's leadership has a significant role in improving the quality of education at MTs Manbatul Fikri Curugrendeng. Strong vision and mission, teacher professional development, good collaboration, and effective resource management are some of the important aspects of principal leadership found in this research.